Paradigma Shift: Revolusi Peran Pustakawan Di Era Teknologi Informasi Masa Kini - Nurjannah, Nur Jannah (LIBRIA, 2018)
The technological advancement of today is so rapidly that librarianscan no longer think that the role of librarians only collects, processesthe collection and presents it to the users and preserves it. It isexactly the old thinking, but times have changed over time. Theexistence of technology leads librarians to change the paradigmfurther ahead for the existence of libraries and the elimination of therole of librarians. The existence of the internet changes the paradigmof information retrieval. This can be seen from the more dominantuse of e-books. The conversion of scientific journals, the effort todigitize the collection and so on. From this phenomenon raisesconcern that the computer can also replace the role of librarians,Internet media facilitate the search for information. Thereforelibrarians are required to follow the changes and adapt to them.Librarians in the information age must be able to adapt to changingusage to meet the needs of users in a relevant, accurate, and fast way.To undertake a change in librarianship, especially concerning theempowerment of human resources and must compete with otherlibrarians in terms of lifting librarian's career and profession withthe latest insights, in accordance with the times and emergingtechnologies. It therefore requires strong commitment andcommitment from the librarian himself as well as the real support ofthe library organization. In the challenge for librarians / librariansto show their identity, by creating new products or services, or oldproducts with new packaging, creativity, new innovations wecombine with the use of information technology, to becomeinformation and change angle for the world of libraries .